The Royal Netherlands Football Association (KNVB) relative age solutions project—part one: a call to action - Kelly, A. L.; Zwenk, F.; Mann, D.; Verbeek, J. (Frontiers in Sports and Active Living, 2025)
Introduction: Despite its widespread prevalence in youth soccer, there seems to be no widely implemented intervention to moderate or overcome Relative Age Effects (RAEs). The purpose of this study was a call to action for stakeholders to propose relative age solutions to the Royal Netherlands Football Association (KNVB).